1995
DOI: 10.1203/00006450-199502000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Water Loss from the Skin of Term and Preterm Infants Nursed under a Radiant Heater

Abstract: The rate of evaporalion from the skin (g/m 2 jh) was measured in 12 full-term and 16 preterm infants (gestational age 25-34 wk) both during incubator care and when nursed under a radiant heater. The method for evaporation rate measurement is noninvasive and based on determination of the water vapor pressure gradient close to the skin surface. Measurements were first made with the infant nursed in an incubator with a controlled environment with respect to humidity, temperature, and air velocity. The measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…The subsequent increase in ceiling temperature resulted in an increase in skin temperature and blood flow and a marked decrease in radiative heat exchange, but did not affect the transepidermal or respiratory water loss. This agrees with previous findings (21), and indicates that the 2 before the hood warmer was switched on. increase in insensible water loss found in some earlier studies (22)(23)(24)(25)(26)(27)(28) was not caused by a direct effect of the non-ionized radiation on the infant's skin, but rather by a lower ambient humidity (28), the presence of convective air currents (29) and/or an increase in motor activity (21) or rate of breathing (30)(31)(32).…”
Section: Discussionsupporting
confidence: 93%
“…The subsequent increase in ceiling temperature resulted in an increase in skin temperature and blood flow and a marked decrease in radiative heat exchange, but did not affect the transepidermal or respiratory water loss. This agrees with previous findings (21), and indicates that the 2 before the hood warmer was switched on. increase in insensible water loss found in some earlier studies (22)(23)(24)(25)(26)(27)(28) was not caused by a direct effect of the non-ionized radiation on the infant's skin, but rather by a lower ambient humidity (28), the presence of convective air currents (29) and/or an increase in motor activity (21) or rate of breathing (30)(31)(32).…”
Section: Discussionsupporting
confidence: 93%
“…It is unfortunate we were unable to study children in the <1-month age range. In an attempt to understand the likely range of values, we compared our results to those presented on nonanesthetized neonates in a series of publications from the University hospital, Uppsala, Swedensome of which we have referred to in this paper (11,14,15). Assuming a birth length of~50 cm and a similar methodology for calculating BSA, they found that TEWL in full-term infants was~1.1 gÁh À1 (at the lower end of our results) and it did not change until 4 weeks (14).…”
Section: Discussionmentioning
confidence: 99%
“…Since the same ambient RH could not be achieved during the measurements for all infants, and to allow comparisons with previous published data, the values obtained for TEWL were corrected to a RH of 1186 J Å gren et al ACTA PAEDIATR 87 (1998) 50% (TEWL 50 ), using the two-point equation for evaporation rate over Ph 2 o at the ambient temperature of each measurement, as presented in a previously published paper (18).…”
Section: Treatment Of Datamentioning
confidence: 99%